Dissemination and Training of Early Childhood Motion Skill Level Development for PAUD / Kindergarten and Elementary Teachers in Lima Puluh Kota District - Lucy Pratama Putri; Ibnu Andli Marta; Oktarifaldi Oktarifaldi; Jonni Jonni; Yulifri Yulifri; Kibadra Kibadra; Ali Asmi; Hasriwandi Nur; Nirwandi Nirwandi; Erizal N; Syahrial Bakhtiar (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2020)
Some of the results of studies that have been conducted on basic early Indonesian fundamental motor skills children, especially in West Sumatra, are found to be at the lowest level. Observations made on several teachers in West Sumatra show that on average they have very limited insight into fundamental motor skills and how to arrange fundamental motor skills. Previous research states that fundamental motor skills cannot develop by themselves, but through continuous learning and training stages. Therefore, PAUD teachers are expected to be skilled in compiling children's fundamental motor skills so that the objectives of early childhood education can be achieved as they should. This service activity aims to: (a) PAUD / TK teachers understand what fundamental motor skills are. (b) PAUD / TK teachers can understand fundamental motor skills. (c) PAUD / TK teachers can understand how to use the TGMD-2 instrument (d) PAUD / TK teachers can understand how to evaluate fundamental motor skills.